Balanced Energy Consumption Approach For Deployment Of Clusters In A WSN - Pal, Debajyoti (I-Manager's Journal on Wireless Communication Networks, 2013)
In this paper we aim to deploy the clusters of a Wireless Sensor Network in such a way so that it leads to a balanced energy consumption. First, we discuss about the radio energy dissipation model [1] that is already in place and the corresponding protocols which are used. Thereafter, we focus on the protocols which are already in practice in such a system, outlining their major disadvantages. Later on, we propose a methodology/algorithm that improves the overall energy consumption which is supported by the results of the experiments carried out by the simulations. Finally, a comparative analysis is done over the results obtained by our algorithm and those which existed previously.